Increased usage of doxycycline for young children with Lyme disease - Amy D. Thompson; Desiree N. Neville; Laura L. Chapman; Fran Balamuth; Meagan M. Ladell; Anupam B. Kharbanda; Rachael Aresco; Lise E. Nigrovic (Frontiers Media S.A., 2024)
BackgroundThe 2018 Infectious Disease Committee of the American Academy of Pediatrics stated that up to 3 weeks or less of doxycycline is safe in children of all ages. Our goal was to examine trends in doxycycline treatment for children with Lyme disease.MethodsWe assembled a prospective cohort of children aged 1 to 21 years with Lyme disease who presented to one of eight participating Pedi Lyme Net centers between 2015 and 2023. We defined a Lyme disease case with an erythema migrans (EM) lesion or positive two-tier Lyme disease serology categorized by stage: early-localized (single EM lesion), early-disseminated (multiple EM lesions, cranial neuropathy, meningitis, and carditis), and late (arthritis). We compared doxycycline treatment by age and disease stage and used logistic regression to examine treatment trends.ResultsOf the 1,154 children with Lyme disease, 94 (8.1%) had early-localized, 449 (38.9%) had early-disseminated, and 611 (53.0%) had late disease. Doxycycline treatment was more common for older children (83.3% ≥ 8 years vs. 47.1% < 8 years; p < 0.001) and with early-disseminated disease (77.2% early-disseminated vs. 52.1% early-localized or 62.1% late; p < 0.001). For children under 8 years, doxycycline use increased over the study period (6.9% 2015 to 67.9% 2023; odds ratio by year, 1.45; 95% confidence interval, 1.34-1.58).ConclusionYoung children with Lyme disease are frequently treated with doxycycline. Prospective studies are needed to confirm the safety and efficacy of doxycycline in children younger than 8 years, especially for those receiving courses longer than 3 weeks.